1999
DOI: 10.1016/s0194-5998(99)70201-9
|View full text |Cite
|
Sign up to set email alerts
|

International Editor: Temporal bone chondroblastoma

Abstract: Chondroblastoma, or so-called benign chondroblastoma, is a relatively rare tumor, accounting for less than 1% of all benign tumors arising from bone. 1,2 This tumor frequently grows within the epiphysis of long bones, but very rarely in the temporal bone. Since Vandenberg and Coley 3 reported the first case of chondroblastoma of the temporal bone in 1950, 33 cases of this tumor have been reported. [4][5][6] This tumor grows aggressively and is characterized by local recurrence and metastasis and should be cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…17,20 However, some authors have reported recurrence rates approaching 20%, even after complete tumor removal. [22][23][24] Therefore, surveillance imaging following surgical resection is prudent for early diagnosis of tumor recurrence. In surgical resection, a conservative approach is recommended with a reduction of postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…17,20 However, some authors have reported recurrence rates approaching 20%, even after complete tumor removal. [22][23][24] Therefore, surveillance imaging following surgical resection is prudent for early diagnosis of tumor recurrence. In surgical resection, a conservative approach is recommended with a reduction of postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lesions of the temporal bone often present with hearing loss (49%), cranial neuropathy (43.3%), facial swelling (22.2%), and/or otalgia (19.8%). 8 12 13 14 15 16 17 18 Since the abducens nerve is particularly prone to compression at the clivus where it enters the Dorello canal, 19 chondroblastoma in this region can result in diplopia with lateral rectus palsy and headache.…”
Section: Discussionmentioning
confidence: 99%
“…The squamous portion of temporal bone is the most common site of craniofacial chondroblastoma, likely due to its cartilaginous origin. 10 17 18 Reid et al identified 81 total reported temporal bone cases since 1950. 12 Only 24 extratemporal craniofacial lesions have been reported previously, including chondroblastoma in the region of the temporomandibular joint ( n = 13), the nasal cavity and paranasal sinuses ( n = 5), skull base ( n = 1), skull vault ( n = 4), and nasion ( n = 1, see Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent immunohistochemical examination of the lesion showed reactivity of the neoplastic protein mass for S-100 protein. The presence of S-100 protein in tumor cells differentiates chondroblastoma from giant cell tumor, chondrosarcoma, and aneurismal bone cysts, favoring the diagnosis of chondroblastoma [8, 9, 10]. The temporal lobes revealed extensive proliferation of multinucleated cells.…”
Section: Discussionmentioning
confidence: 99%